2020
DOI: 10.1038/s41598-020-61983-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the deuterium on efficiency and type of adipogenic differentiation of human adipose-derived stem cells in vitro

Abstract: In this study, we performed an adipogenic differentiation of human adipose-derived stem cells (ADSCs) in vitro with different deuterium content (natural, low and high) in the culture medium during differentiation process with parallel analysis of the gene expression, metabolic activity and cell viability/ toxicity. After ADSCs differentiation into adipocytes we have done the analysis of differentiation process efficiency and determined a type of resulting adipocytes (by morphology, gene expression, UCP1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…The deuterium concentration in the body plays an important role in the metabolic processes of living systems [ 1 , 2 , 3 , 4 ]. The biological effects caused by deuterium depleted water (DDW) have been studied at various levels: cellular [ 5 , 6 , 7 , 8 ], tissue [ 9 ], organismic [ 10 , 11 , 12 , 13 , 14 ]. It was found that low concentrations of deuterium in the drinking diet increase stress resistance in mammals [ 15 ], and may also have neuroprotective properties [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deuterium concentration in the body plays an important role in the metabolic processes of living systems [ 1 , 2 , 3 , 4 ]. The biological effects caused by deuterium depleted water (DDW) have been studied at various levels: cellular [ 5 , 6 , 7 , 8 ], tissue [ 9 ], organismic [ 10 , 11 , 12 , 13 , 14 ]. It was found that low concentrations of deuterium in the drinking diet increase stress resistance in mammals [ 15 ], and may also have neuroprotective properties [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of changes in the vital indicators of the organisms in the deuterium-depleted water environment does not give a definite clear correlation. Some biological effects of water with a modified isotopic composition was presented earlier [ 1 , 17 , 19 , 22 , 23 , 24 , 25 ]. The results of deuterium-depleted water exposure on the lower and higher plants, not previously published considered below.…”
Section: Resultsmentioning
confidence: 99%
“…Broad varieties of morphological and physiological changes were observed in deuterium-treated cells and organisms, including changes in fundamental processes such as cell division or energy metabolism [ 56 ]. However, it should be noted that we showed before how an excessive deficiency or an excess of deuterium can cause cytotoxic effects at the cell level [ 23 , 57 ]. Therefore, additional research of the use of water with a reduced deuterium content is required.…”
Section: Resultsmentioning
confidence: 99%
“…In the deuterated nutrient medium, a decrease in the metabolic activity is observed on the third day, and in the deuterium-depleted medium, an increase in the viability of the ADSCs culture is noted. The differentiation of ADSCs into adipocytes was also carried out under the conditions of different deuterium contents in the nutrient medium [36]. It was found that a high (5 • 10 5…”
Section: Cell Culturesmentioning
confidence: 99%
“…Thus, deuterium was considered as an element that affects the chirality of a substance in biological models in vitro/in vivo [4,7,15,27,36].…”
Section: Cell Culturesmentioning
confidence: 99%